Association between metabolic syndrome and periodontitis: a systematic review and meta-analysis - Luciana Dondonis Daudt; Marta Liliana Musskopf; Marina Mendez; Luciana Loss Reck Remonti; Cristiane Bauermann Leitão; Jorge Luiz Gross; Patricia Weidlich; Rui Vicente Oppermann (Brazilian Oral Research, 2018)
Abstract The aim of the present study was to evaluate the association between metabolic syndrome (MS) and periodontitis (PD), through a systematic review and meta-analysis. Original observational studies assessing the association between MS and PD in adults, published before May 11th (2017), were identified through electronic searches of MEDLINE, EMBASE and Cochrane Library databases. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guideline was used. For studies to be included, they had to mention the criteria used to diagnose MS and to have used at least one clinical measure to diagnose PD. There was no language restriction. Three reviewers independently identified eligible studies for possible inclusion in the systematic review and meta-analysis. The quality of the studies was evaluated by the Newcastle-Ottawa scale for observational studies. A random model meta-analysis was conducted. The strategies used to investigate heterogeneity were sequential analysis, subgroup analysis, univariate meta-regression and sensitivity analysis. Thirty-three studies met the inclusion criteria for the systematic review, and 26 had enough information to be included in the meta-analysis, totaling 52,504 patients. MS and PD were associated with an odds ratio of 1.38 (95%CI 1.26–1.51; I2 = 92.7%; p < 0.001). Subgroup analysis showed that complete periodontal examination (I2 = 70.6%; p < 0.001) partially explained the variability between studies. The present findings suggest an association between MS and PD. Individuals with MS are 38% more likely to present PD than individuals without this condition. Prospective studies should be conducted to establish cause and effect relations between MS and PD.